The Development Of Tourism Sector As A Strategy To Increase Local Revenue Surakarta: Pengembangan Sektor Pariwisata Sebagai Strategi Meningkatkan Pendapatan Asli Daerah Kota Surakarta - Arsita, Nurul Cahya; Ahmadi, Mirzam Arqy (Badan Riset dan Inovasi Daerah Kota Surakarta, 2024)
This study aims to analyze the role of tourism sector development as a strategy to increase the Regional Original Revenue (PAD) of Surakarta City. Tourism is one of the economic sectors with significant potential to contribute to regional income growth. This research employs a literature study method with a quantitative data approach, based on secondary data analysis from official reports by the Surakarta City government and related agencies, covering target and realization data of PAD and tourism sector contributions from 2022 to 2023. The analysis results indicate an increase in PAD realization from the tourism sector, although the overall PAD target has not been fully achieved. The tourism sector’s contribution to PAD has shown a consistently positive impact, with substantial progress toward meeting targets. Based on these findings, it can be concluded that tourism sector development plays an essential role in driving the local economy and significantly contributes to Surakarta City's PAD. This study is expected to serve as a reference for local governments in developing sustainable strategies to strengthen the tourism sector as a primary source of revenue.